Active tectonics in the Main Boundary Thrust zone, Garhwal Himalaya, as evident from palaeoseismic signatures, morphotectonic features and PSI base ground deformation. Issue 1 (14th September 2022) - Luirei, Khayingshing; Ch. Kothyari, Girish; Mehta, Manish
Abstract : In the Garhwal Himalaya, the steeply inclined Main Boundary Thrust (MBT) is characterized by landforms that indicate towards tectonic activity in the recent past. Linear active fault trace, sub‐recent fault scarps, strath terrace, uplifted terraces, deflected drainage, and triangular facet cones are some of the morphotectonic evidences of recent tectonic activity along the MBT. The MBT is defined by active fault trace in the form of linear depression and shows a prominent slope break across it. Thrusting of the Lesser Himalayan bedrocks over the colluvial deposits and back tilting of the colluvial deposits are also observed in the MBT zone. The formation of the sag pond and the deposition of the Quaternary lacustrine sediments followed by the deformation of the lacustrine deposits indicate phases of tectonic activities along the MBT. The later phase of deformation is represented by the folded lacustrine and colluvial deposits, where the amplitude of the fold measures about 3 m‐high and the deformed section measures about 23 m in length. The ongoing deformation patterns of the MBT zone have also been monitored with the help of Synthetic Aperture Radar‐based time series analysis. We used Sentinel‐1C dataset in ascending direction with polarization of the VV+ VH acquired between December 2, 2017 to September 7, 2021 to identify phase changes caused by ongoing active deformation. The Persistent Scatterer Interferometry (PSI) result based on Sentinel‐1A suggests that the Dehradun–Mussoorie and adjoining region has undergone an average deformation of 5.5 to −11 mm/year and the ground displacement of 1.5 to −3.8 cm. The time series analysis reveals that the Mussoorie hills in the MBT zone have higher rate of deformation. Abstract : The present study is the theme at presenting the evidence that pertains to have been formed as a result of seismic activity along the MBT in the recent past which will be the first of its kind from the MBT and also active deformations based on PSI analysis and morphotectonic.